Hodgkin's Lymphoma in Crohn's Disease Treated with Infliximab - Carvalho, D (2017)
INTRODUCTION: Lymphoproliferative disorders, particularly non-Hodgkin's and Hodgkin's lymphomas, are rare in patients with inflammatory bowel diseases. The use of thiopurines and infection by Epstein-Barr virus are well-known cofactors that can raise its prevalence. Other risk factors such as disease activity and biological treatment are the subject of discussion, without enough data in the literature to confirm a potential association. METHODS: We report a case of Hodgkin's lymphoma in a patient who had been treated with azathioprine and was on long-term monotherapy with infliximab. CONCLUSIONS: We stress the importance of recognizing the possible occurrence of a lymphoproliferative disorder in association with anti-tumor necrosis factor-α therapy.